Characteristics of mothers with children diagnosed with Congenital Syphilis - Mayara Nascimento de Vasconcelos; Maria Adelane Monteiro da Silva; Thereza Maria Magalhães Moreira; Andréa Carvalho Araújo Moreira; Cibelly Aliny Siqueira Lima Freita; Raquel Sampaio Florêncio; Maria Lúcia Duarte Pereira (O Mundo da Saúde, 2020)
The development of health actions based on social, cultural, and economic aspects is essential. Thus, the objective of the study was to identify the socioeconomic and clinical characteristics of mothers with children diagnosed with Congenital Syphilis. This is a cross-sectional study, carried out with notification forms of congenital syphilis, from 2010 to 2017 in a health region in Northeast Brazil, totaling 522 cases. A higher percentage of vertical transmission was identified in young women, with a median age of 23 years, 92% (f=480) of mothers declared themselves as a brown-skinned, 75.7% (f=395) were housewives, and 44.1% (f=230) had an incomplete 5th to 8th grade education. Regarding the clinical characteristics, it was found that 94.6% (f=494) performed prenatal care, however, less than half (46.9%; f=245) were diagnosed within the same period, and 55.6% (f=290) received an inadequate treatment of syphilis. It was also observed that, with regards to the association of the characteristics of these pregnant women and prenatal care, a significant difference in the “diagnosis of maternal syphilis” (p: 0.001) and “treatment scheme” (p: 0.0001). Thus, the results of this study are essential for the health planning of the municipalities, which reinforces the importance of these indicators and of the situations of vulnerabilities during prenatal care, and it is also opportune to have permanent education with professionals, so that they recognize the use of these findings as tools for health practice.